Evaluation of Lead and Cadmium Concentrations in The Muscles of Four Fish Species from Ain Al-Ghazala Lagoon, Libya - El-Mabrok, Mohammad; Alfergani, Eman Salem; Mohammed, Najlaa F.; Mohammed, Yahya A.; Muhammad, Aya I.; Majeed, Mariam A. (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2025)
Evaluation of lead and cadmium concentrations in the muscles of four fish species: Trigla lucerna, Lithognathus mormyrus, Siganus rivulatus, Liza saliens, collected from Ain AL-Ghazala Lagoon, eastern Libya, during the summer of 2022, were analyzed by Atomic absorption spectrophotometer. The results indicated that the concentration of lead was ranged from 0.1485±0.0278 ppm in L. mormyrus to 0.2533±0.0044 ppm in L. saliens. The cadmium accumulation was ranged from 0.0004±0.000 to 0.0026±0.000 ppm in L. saliens, T. lucerna respectively. There was a significant positive correlation between the condition factor and the concentration of lead and cadmium in L. saliens and cadmium in T. lucerna. And there was a negative significant correlation between lead and cadmium in T. lucerna, while S. rivulatus and L.saliens recorded a positive significant correlation. We found a positive significant relationship between fish length and metals only in S. rivulatus (Cd; R2:0.76, Pb; R2: 0.56) and a negative significant relationship between length and cadmium in L. saliens (R2:-0.69). The estimated daily intake results for lead and cadmium ranged between 0.1056 mg.day-1 to 0.1802 mg.day-1 and 0.0002 mg.day-1 to 0.00187 mg.day-1. The mean of target hazard quotients and total target hazard quotient are below 1.00, so no adverse health effects are expected.